Representações do Brasil em reportagens jornalísticas estadunidenses sobre rompimentos de barragens em Minas Gerais - Felipe José Fernandes Macedo (2022)
This research is part of the theoretical and methodological line of multimodal discourse, a subfield of Linguistics. The general objective was to analyze representations of Brazil from the point of view of a developed country, in this case the United States. For this, we started from a linguistic and sociosemiotic investigation that considered in its analysis the choices made by the producers of journalistic texts published in different American news portals that narrate the ruptures of the Fundão dam in Mariana and the Mina do Feijão (B1) dam in Brumadinho. Eight texts about those two social events were analyzed. The theoretical framework is anchored in Social Semiotics (HODGE; KRESS, 1988; HODGE, 2017), in the Multimodality approach (KRESS; VAN LEEUWEN, 2001, 2021), in Systemic-Functional Linguistics (HALLIDAY; 1985; HALLIDAY; MATTHIESSEN, 2014) and in Spatial Discourse Analysis (STENGLIN, 2004; 2009; RAVELLI; MCMURTRIE, 2016), especially in the categories, binding and bonding. In the analyzed texts, Brazil is represented in a negative light, more precisely as a negligent country in relation to the safety of its dams and hostage to the revenues generated by the mining-export sector, which prevents the implementation of stricter environmental legislation on that sector. The analyses also indicate that, by having his house destroyed by the mud, the inhabitant loses not only his material and family patrimony, but also his own sense of security in the world, since this built space is, in spatial terms, responsible for making him feel safe and protected. On the other hand, although the mud is an element that causes death and destruction, it also fulfills the socio-semiotic function of promoting union and solidarity among the users of the three-dimensional spaces affected, in this case the residents of the regions around the dams that survived the disasters.